Energy transactions based on distributed ledger technologies for renewable energy communities - Andrade, Daniel Baptista (2023)
The emergence of renewable energy communities, in combination with the transition from fossil fuels to sustainable energy sources, has empowered the emergence of a new paradigm in which energy is exchanged in a decentralized manner among community members, known as prosumers. Alongside this idea of decentralization, the concept of Distributed Ledger Technology, an emerging technology designed to decentralize information across a network of devices that allows for verifying the truthfulness of its content, also arises. In addition to storing information, this technology also enables digital currency exchanges, known as cryptocurrencies. This work proposes to apply these new concepts to a renewable energy community through direct transactions or via smart contracts among community members who sell excess energy production, without the need for intervention from a network operator or a banking entity. It is intended that by using Distributed Ledger Technologies, a mechanism capable of creating a history of events within the community can be established while enabling payments among its members at more competitive prices than those in the traditional market.